Team building and hidden costs of control - Gerhard Riener; Simon Wiederhold (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper investigates the interaction of intrinsic and extrinsic incentives. We propose a simple principal-agent model with control that incorporates the existence of social groups resulting from common experiences in the past. Our laboratory experiment shows that agents with previous common experiences with their principals (CE agents) perform better than agents without such experiences (NCE agents). However, as soon as actual control exceeds their expectation, CE agents decrease their performance substantially, which has no equivalent for NCE agents. This pronounced decrease in effort when control is perceived as excessive represents a novel channel through which hidden costs of control materialize. Our results have important implications for firms' strategies to motivate employees.
Keywords: C92; M54; D03; J22; 330; Employee motivation; Principal-agent theory; Experiments